Managing the COVID-19 Pandemic in a Fragmented Local Government Setting: a Study from Ogan Ilir Regency, Indonesia - Faisal Nomaini; Hoirun Nisyak; Anang Dwi Santoso (Universitas Muhammadiyah Yogyakarta, 2022)
The COVID-19 pandemic marks the importance of coordination, cooperation, and collaboration to reduce the virus’ spread and its impacts. Although a lot of literature has explored how the government works during the COVID-19 pandemic, only a few studies have examined it at the local government level. Therefore, this study aims to fill this gap by exploring the local government’s workings and the agencies. This study used narrative qualitative research with the main data source from interviews with the Ogan Ilir Regency COVID-19 Task Force for the Acceleration of Response. This study found that government agencies have not accomplished at the action level despite having a common goal as a condition of coordination. The findings of this study reaffirmed that the silo mentality still exists in the bureaucracy of local government in Indonesia.